Talempong in the Context of Minang Cultural Heritage: Phenomenological Study Based on Nvivo 12 Plus - Rina Armeniza Aziz (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This research is motivated by the fact that today's younger generation is more familiar with modern pop music, K-Pop, and various digital music genres than talempong, as well as low participation. This study aims to determine talempong's function as a symbol of Minang cultural identity, the challenges faced in preserving it amidst globalization, and strategic efforts undertaken to maintain its transmission across generations. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 15 informants consisting of traditional musicians, cultural figures, art educators, and tourism practitioners in West Sumatra. Data collection techniques included interviews, observation, and documentation. Data analysis was conducted using NVivo 12 Plus software, which allows systematic coding, thematic grouping, and pattern identification from a rich qualitative data set. The findings indicate that talempong occupies a sacred and functional role in Minang ceremonial life. At the same time, it faces existential threats from the proliferation of digital entertainment and declining interest from the younger generation. The study identified three interrelated preservation strategies: institutional integration through formal arts education curriculum, commercialization through cultural tourism, and community-based revitalization through traditional institutions. This research contributes theoretically to the discourse on intangible cultural heritage and practically to heritage tourism policy in Indonesia. The findings suggest that a hybrid model combining traditional transmission with digital documentation and a creative economic approach offers the most sustainable path to talempong preservation.